Peran Kelompok Nelayan Dalam Aktivitas Pariwisata Di Desa Kedonganan Kuta, Bali - Lisbet Sihombing; Saptono Nugroho (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
This research is motivated by the important roles of the Kedonganan people to gather in a fishing group community to develop of tourism activityin Kedonganan Beach. Fishermen Group in Kedonganan Beach is required to become a tourism actors with many demands of tourists that visiting to Kedongananvillage of FishermenGroup.The purpose of this research to find out the forms of involvement or the roles by fishermen group in supporting the tourism activity ini Kedonganan village. The type of data in this study usedescriptive qualitative. Data collection techniques use in this research are interviews, study documentsorliterature.Techniques of informan determining use dept interviews with determining the key informan. The key informant which is selected in this study is Putra Bali’s Fishermen Group in Kedonganan village. The data analysis techniques are uingData Reduction, Data Display, and Conclusion Drawing/Verification. The research concludes that fishermen group hasan important role in tourism activity in Kedongananvillage, there arein economic, social, cultural, environmental, and political. But there are problemsof the role of the fishermen in the field of the environment, because it is less in keeping it clean, the plastic waste and used garbage incinerator make badsights and the sand starts to dirty.The fishing groups should form a section in them organizational structure that works specifically to maintain the cleanliness of the beach area. They should alsoadd some attractions, which besides being a tourist guide who wants to see the beauty beneath the sea, the fishing activity such as knitting nets can also be used as an educational tour on marine fisheries. Thus, tourists canalso invited to participate in fishing activity, and diving to study marine tourism, and preservation. Keywords : Comunity Based Tourism (CBT), Fishermen Group, Role of Fishermen Group